Gene Expression - Uchiumi, Fumiaki (IntechOpen, 2022)
Gene expression is dependent on multiple steps, including transcription, RNA processing, and translation. Importantly, recent studies revealed that gene expression is regulated by chromatin structures and non-coding RNA profiles. Elucidating the molecular mechanisms may contribute to the development of novel therapeutics for aging-related diseases, including cancer and neurodegenerative diseases. This book provides a comprehensive overview of gene expression and its role in human disease. It consists of nine chapters organized into two sections on molecular mechanisms in controlling gene expression and the relationships between transcriptional control and human disease.